The Effectiveness of Long-Time Blanching on The Quality of Avocado Leaf Herbal Tea Added with Cinnamon Powder - Ristia, Jeany; Hersamila, Riztiva; Efendi, Raswen; Dewi, Yossie Kharisma (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Herbal tea is a beverage prepared from plant materials other than Camellia sinensis and has gained attention due to its functional properties. Avocado (Persea americana) leaves are a potential raw material for herbal tea because they contain bioactive compounds with antioxidant activity. This study evaluated the effect of blanching time on the quality of avocado (Persea americana) leaf herbal tea and determined the optimal treatment. A randomized controlled experiment was conducted using four blanching durations (0, 5, 10, and 15 min) with 16 experimental units. Moisture content, ash content, antioxidant activity, tannin content, and sensory acceptance were analyzed. Statistical analysis was performed using ANOVA followed by Duncan’s Multiple Range Test at a 5% significance level. Blanching time significantly affected the physicochemical and sensory properties of the herbal tea. The 15-minute blanching treatment produced the best quality, with moisture content of 4.11%, ash content of 6.46%, antioxidant activity of 41.66 ppm (very strong), and tannin content of 0.0121%. Sensory evaluation showed a yellow color, a slightly stale aroma, a non-bitter taste, and moderate overall acceptance. These results indicate that 15-minute blanching is optimal for producing high-quality avocado leaf herbal tea.